A ceramsite filter material for treating fluorine-containing wastewater and its preparation method and application
By mixing coal gasification slag, coal gangue, calcium carbide slag and hydroxyapatite in a specific proportion, microwave sintering and hydrothermal treatment, ceramic filter material with high porosity and strength was prepared, which solved the problem of poor fluorine removal effect of the existing adsorption method and achieved efficient and economical fluorine removal effect.
Patent Information
- Application Number
- CN202411741255.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-01
AI Technical Summary
The existing adsorption method has poor fluorine removal effect, and the powder adsorbent is easy to form, agglomerate, and is difficult to recycle, and is easily affected by other ions, resulting in poor fluorine removal effect.
By mixing coal gasified slag, coal gangue, calcium carbide slag and hydroxyapatite in a specific proportion, microwave sintering, immersing it in a phosphate solution for hydrothermal treatment, ceramic filter material with high porosity and strength was prepared, and the hydroxyapatite was loaded in situ to adjust its crystal structure to improve fluorine removal performance.
It achieves efficient fluorine removal, avoids the problems of plate bonding and agglomeration of powder adsorbents, improves the selectivity and efficiency of fluorine removal, reduces costs, and is easy to achieve industrial production.
Smart Images

Figure CN119735449A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, and in particular to a ceramsite filter material for treating fluorine-containing wastewater, and a preparation method and application thereof. Background Art
[0002] Gangue is a type of industrial waste generated during coal mining, gasification slag is the residual product after high-temperature gasification of coal in the coal chemical process, and carbide slag is the fine ash collected in the boiling furnace after carbide is hydrolyzed to obtain acetylene gas. At present, the stock of industrial solid wastes such as gasification slag, gangue and carbide slag in central and western Inner Mongolia is huge. Under the current policy background, high-value and efficient utilization is imperative. At the same time, there are many coal mines in the region, and the underground wastewater of coal mines generally has a high fluoride content. The mining process of ores and coal mines is often accompanied by the discharge of high-concentration fluoride-containing mine water. If it is directly discharged without treatment, it will cause serious fluoride pollution problems in water bodies. The intake of a small amount of fluoride can promote the resistance of teeth to bacterial acid corrosion and prevent tooth decay, but when the intake of fluoride exceeds the normal amount required by the human body, it will cause chronic poisoning of the body, and symptoms such as bone deformation, pain in the waist and leg joints, and spinal cord compression will appear. Therefore, my country stipulates that the fluorine content of coal mine water must meet the Class III requirements of the "Surface Water Environmental Quality Standard" (GB3838-2002), that is, the fluorine concentration of the water must be ≤1mg / L, but the fluorine content of untreated mine water often exceeds the limit. Therefore, it is necessary to find a practical and efficient method of fluorine removal to solve the above problem.
[0003] At present, the main methods for removing fluoride from aqueous solutions include lime precipitation, electrocoagulation, ion exchange, electrodialysis, membrane separation, adsorption, etc. Among them, adsorption is regarded as an effective method for defluoridation due to its simple operation, stable operation and low cost. The key to defluoridation by adsorption is the adsorbent. Activated alumina, activated carbon, hydroxyapatite (HAP), etc. have been widely studied and applied to fluoride wastewater treatment. Activated alumina is the most widely used defluoridation adsorbent due to its low cost and high adsorption efficiency, but its biggest disadvantage is that it is easy to harden, and residual aluminum fluoride complexes and a large amount of sludge are produced during the adsorption process, causing secondary pollution; although activated carbon has a developed pore structure and a large specific surface area, its adsorption selectivity is poor, the defluoridation capacity is low, and regeneration is difficult; hydroxyapatite has strong ion exchange and adsorption properties, and a high defluoridation capacity, but it is easy to agglomerate during use, and the defluoridation capacity decreases rapidly after balling, which will also increase the turbidity of water. At the same time, adsorbents in powder form are difficult to recycle after adsorption, and dispersion in water will also cause system blockage and ultimately increase the pressure drop of the entire fluorine adsorption column. In addition, most current adsorbents are also susceptible to the competitive influence of other ions (such as carbonate ions and sulfate ions) on the removal of fluoride ions during the defluorination process, which in turn leads to poor defluorination effect of the adsorbent. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the existing adsorption method, that is, the powder adsorbent is easy to compact and agglomerate and is difficult to recycle, thereby providing a ceramsite filter material for fluorine-containing wastewater treatment and its preparation method and application to solve the above problems.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a ceramsite filter material for treating fluoride-containing wastewater, comprising:
[0007] 50-65 parts by weight of coal gasification slag, 10-15 parts by weight of coal gangue, 25-35 parts by weight of carbide slag and 5-10 parts by weight of hydroxyapatite are weighed and mixed to obtain a mixture, and then granulated and microwave sintered to obtain sintered ceramsite; wherein the heat treatment system of the microwave sintering is: firstly heating to 650-750° C. for pre-sintering treatment, and then heating to 1020-1080° C. for sintering treatment;
[0008] The sintered ceramsite is immersed in a phosphate solution for hydrothermal treatment, and then subjected to aging treatment to obtain the ceramsite filter material.
[0009] Preferably, the SiO in the coal gasification slag 2 :42-50wt%, Al 2 O 3 : 3-20wt%, CaO: 2-18wt%, Fe 2 O 3 : 1-15wt%, carbon: 10-30wt%;
[0010] And / or, SiO in the coal gangue 2 :40-60wt%、Al 2 O 3 : 35-50wt%;
[0011] And / or, the carbide slag contains 35-60wt% CaO and 20-30wt% MgO.
[0012] Preferably, the particle size of the coal gasification slag, coal gangue, carbide slag and hydroxyapatite is ≤100 μm;
[0013] and / or, the binder used in the granulation step is a polyvinyl alcohol aqueous solution;
[0014] and / or, the concentration of the binder used in the granulation step is 0.7-1wt%;
[0015] and / or, the mass ratio of the mixture to the binder in the granulation step is 1:(17-25);
[0016] And / or, the granulation step is followed by a drying process.
[0017] Preferably, the heating rate of the pre-sintering treatment is 140-160°C / min;
[0018] And / or, the duration of the pre-sintering treatment is 5-8 minutes;
[0019] And / or, the heating rate of the sintering treatment is 45-55°C / min;
[0020] And / or, the sintering treatment time is 5-10 min;
[0021] And / or, the sintering process is followed by furnace cooling.
[0022] Preferably, the aging treatment lasts for ≥ 6 hours;
[0023] And / or, the aging treatment is followed by washing and drying treatment;
[0024] And / or, the strength of the sintered ceramsite is 5-10 MPa;
[0025] And / or, the apparent porosity of the sintered ceramsite is 42-55%.
[0026] Preferably, the hydrothermal treatment process comprises: firstly immersing the sintered ceramsite in deionized water until the pH value of the system is 9.5-10.5, and then adding phosphate and acetylacetone for hydrothermal treatment.
[0027] Preferably, the mass ratio of the sintered ceramsite to deionized water is 1:(6-8);
[0028] And / or, the mass ratio of the sintered ceramsite to the phosphate is (40-60):1;
[0029] And / or, the mass ratio of the deionized water to acetylacetone is 100:(2-4).
[0030] Preferably, the phosphate is diammonium phosphate and / or ammonium hydrogen phosphate;
[0031] And / or, the immersion temperature is 60-80°C;
[0032] And / or, the temperature of the hydrothermal treatment is 90-120°C;
[0033] And / or, the duration of the hydrothermal treatment is 4-5 hours.
[0034] The present invention also provides a ceramsite filter material for treating fluorine-containing wastewater, which is prepared by the above-mentioned method for preparing the ceramsite filter material for treating fluorine-containing wastewater.
[0035] The present invention also provides application of the above-mentioned ceramsite filter material for treating fluorine-containing wastewater in treating fluorine-containing wastewater.
[0036] The technical solution of the present invention has the following advantages:
[0037] 1. A method for preparing ceramsite for treating fluorine-containing wastewater, comprising: weighing 50-65 parts by weight of coal gasification slag, 10-15 parts by weight of coal gangue, 25-35 parts by weight of carbide slag and 5-10 parts by weight of hydroxyapatite, mixing them evenly to obtain a mixture, granulating them, and subjecting them to microwave sintering to obtain sintered ceramsite; wherein the heat treatment system of the microwave sintering is: first heating the temperature to 650-750° C. for pre-sintering treatment, and then heating the temperature to 1020-1080° C. for sintering treatment; immersing the sintered ceramsite in a phosphate solution for hydrothermal treatment, and then subjecting the sintered ceramsite to aging treatment to obtain a ceramsite filter material. The present invention, without using any additional additives, obtains a ceramsite filter material with large porosity, high strength and specific crystal phase composition by regulating the raw material ratio of coal gangue, coal gasification slag, carbide slag and hydroxyapatite and the microwave sintering heat treatment system, and achieves efficient disposal of industrial solid wastes of coal gangue, coal gasification slag and carbide slag while solving the actual needs of local fluorine-containing mine wastewater treatment. In addition, the present invention is also designed based on the fact that HAP belongs to the P1121 / b crystal structure, and the Ca ions on the low-energy crystal plane of the structure are relatively less exposed, which limits its adsorption effect on F ions. While hydroxyapatite is in-situ loaded on the surface of the sintered ceramsite, more large ion radius elements (Fe, Al, etc.) in the industrial solid waste are fixed on the hydroxyapatite (Ca) through microwave treatment. 10 (PO)6(OH)) lattice interstitial position, these large ion radius elements greatly increase the unit cell constant of HAP, causing huge structural distortion of HAP structure, resulting in the length of Ca-O bond in HAP being lengthened, reducing the adsorption energy of F atoms in HAP. At the same time, this structure also changes the formation energy of each interface of the material, and the Ca ions of the material as a whole tend to be enriched on the exposed surface of the crystal. Based on the above reasons, the ceramsite filter material loaded with HAP in situ has great benefits in the treatment of fluorine-containing wastewater.
[0038] 2. The ceramsite filter material for treating fluorine-containing wastewater prepared by the present invention is a slow-release ceramsite, which can slowly provide Ca in water while maintaining the ceramsite itself with a large porosity and high strength. 2 +, and maintain an alkaline environment, which provides favorable conditions for further loading HAP on ceramsite to supplement the phosphorus defects in hydroxyapatite during microwave sintering treatment, thereby improving the fluorine removal performance of ceramsite. Therefore, the ceramsite synthesized by microwave sintering only needs to be immersed in a phosphate solution for a period of time, and its inner and outer surfaces can form HAP with small grain size and good dispersion, giving full play to the exchange capacity of HAP ion exchange for fluorine ions, improving the exchange efficiency, enhancing the selectivity of the adsorption process, overcoming the insufficient fluorine removal capacity of ceramsite itself and the influence of other ions interference in the fluorine removal process, and avoiding the turbidity and dispersion in water that cause the system to block and increase resistance and difficult to recycle when the powder HAP is adsorbed. In addition, the calcium ions slowly released by the ceramsite filter material in water react with fluorine ions to generate insoluble calcium fluoride, thereby further increasing the fluorine removal capacity. The ceramsite filter material prepared by the present invention is essentially a HAP / ceramsite composite material, which has the functions of physical filtration and chemical adsorption, combines the advantages of ceramsite and HAP, and has a simple preparation process, saves raw materials, has extremely low cost, and is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 This is a process diagram for preparing the ceramsite filter material used for treating fluorine-containing wastewater in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0042] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0043] In the following examples and comparative examples, SiO 2 :43-49wt%, Al 2 O 3 :8-15wt%, CaO: 10-15wt%, Fe2 O 3 : 4-10wt%, carbon: 19-26wt%; SiO in the gangue 2 :42-50wt%, Al 2 O 3 : 40-45wt%; the carbide slag contains 45-52wt% CaO and 23-29wt% MgO.
[0044] Example 1
[0045] This embodiment provides a method for preparing a ceramsite filter material for treating fluorine-containing wastewater. The process route is as follows: Figure 1 As shown, the following steps are included:
[0046] 1) Coal gasification slag, coal gangue, carbide slag and hydroxyapatite are crushed and sieved respectively by a crushing device to obtain powder with a particle size of ≤100 μm, 65 parts by weight of coal gasification slag powder, 10 parts by weight of coal gangue powder, 25 parts by weight of carbide slag powder and 5 parts by weight of hydroxyapatite are fully mixed in a mixing device, and then placed in a round pot granulator for granulation, 18 parts by weight of a polyvinyl alcohol aqueous solution with a mass fraction of 0.7% is added during the granulation process, and after the granulation is completed, it is dried at room temperature for 48 hours, and the obtained raw material balls are placed in a microwave sintering furnace, and the temperature is increased from room temperature to 650°C at a heating rate of 140°C / min and kept warm for 5 minutes, and then the temperature is increased to 1050°C at a heating rate of 45°C / min and kept warm for 5 minutes, and then naturally cooled with the furnace to obtain sintered ceramsite, and the strength of the sintered ceramsite is 6.78MPa and the apparent porosity is 43.80%;
[0047] 2) 60 parts by weight of the sintered ceramsite obtained in step 1) are placed in a hydrothermal treatment kettle filled with 400 parts by weight of deionized water, and the temperature of the hydrothermal treatment kettle is maintained at 60° C. After immersion for 50 hours, the pH of the system reaches 9.51, and ammonium hydrogen phosphate and acetylacetone are added to the hydrothermal treatment kettle. The amount of ammonium hydrogen phosphate added is 1 part by weight, and the mass ratio of deionized water to acetylacetone is 100:3. The hydrothermal treatment kettle is then quickly heated to 100° C. and reacted for 5 hours. Stirring was continued during the reaction. After the reaction was completed, the ceramsite was aged for 6 hours to take out, washed with deionized water 5 times, and dried in a constant temperature drying oven at 120° C. for 3 hours to obtain a ceramsite filter material.
[0048] Example 2
[0049] This embodiment provides a method for preparing a ceramsite filter material for treating fluorine-containing wastewater, comprising the following steps:
[0050] 1) Coal gasification slag, coal gangue, carbide slag and hydroxyapatite are crushed and sieved respectively by a crushing device to obtain powder with a particle size of ≤100 μm, 50 parts by weight of coal gasification slag powder, 10 parts by weight of coal gangue powder, 30 parts by weight of carbide slag powder and 10 parts by weight of hydroxyapatite are fully mixed in a mixing device, and then placed in a round pot granulator for granulation, 22 parts by weight of a polyvinyl alcohol aqueous solution with a mass fraction of 0.7% is added during the granulation process, and after the granulation is completed, it is dried at room temperature for 48 hours, and the obtained raw material balls are placed in a microwave sintering furnace, and the temperature is increased from room temperature to 750°C at a heating rate of 150°C / min and kept warm for 5 minutes, and then the temperature is increased to 1080°C at a heating rate of 50°C / min and kept warm for 10 minutes, and then naturally cooled with the furnace to obtain sintered ceramsite, and the strength of the sintered ceramsite is 8.18MPa and the apparent porosity is 45.84%;
[0051] 2) 60 parts by weight of the sintered ceramsite obtained in step 1) are placed in a hydrothermal treatment kettle filled with 480 parts by weight of deionized water, and the temperature of the hydrothermal treatment kettle is maintained at 80° C. After immersion for 60 hours, the pH of the system reaches 9.88, and ammonium dihydrogen phosphate and acetylacetone are added to the hydrothermal treatment kettle. The amount of ammonium dihydrogen phosphate added is 1.2 parts by weight, and the mass ratio of deionized water to acetylacetone is 100:2. The hydrothermal treatment kettle is then quickly heated to 110° C. and reacted for 4 hours. The reaction was continuously stirred. After the reaction was completed, the ceramsite was aged for 6 hours to take out, washed with deionized water 5 times, and dried in a constant temperature drying oven at 120° C. for 4 hours to obtain a ceramsite filter material.
[0052] Example 3
[0053] This embodiment provides a method for preparing a ceramsite filter material for treating fluorine-containing wastewater, comprising the following steps:
[0054] 1) Coal gasification slag, coal gangue, carbide slag and hydroxyapatite are crushed and sieved respectively by a crushing device to obtain powder with a particle size of ≤100 μm, 50 parts by weight of coal gasification slag powder, 15 parts by weight of coal gangue powder, 35 parts by weight of carbide slag powder and 5 parts by weight of hydroxyapatite are fully mixed in a mixing device, and then placed in a round pot granulator for granulation, 25 parts by weight of a 1% polyvinyl alcohol aqueous solution is added during the granulation process, and after the granulation is completed, it is dried at room temperature for 48 hours, and the obtained raw material balls are placed in a microwave sintering furnace, and the temperature is increased from room temperature to 650°C at a heating rate of 160°C / min and kept warm for 8 minutes, and then the temperature is increased to 1020°C at a heating rate of 55°C / min and kept warm for 10 minutes, and then naturally cooled with the furnace to obtain sintered ceramsite, and the strength of the sintered ceramsite is 5.87MPa and the apparent porosity is 48.84%;
[0055] 2) 60 parts by weight of the sintered ceramsite obtained in step 1) are placed in a hydrothermal treatment kettle filled with 450 parts by weight of deionized water, and the temperature of the hydrothermal treatment kettle is maintained at 80° C. After immersion for 70 hours, the pH of the system reaches 10.30, and ammonium hydrogen phosphate and acetylacetone are added to the hydrothermal treatment kettle. The amount of ammonium hydrogen phosphate added is 1.5 parts by weight, and the mass ratio of deionized water to acetylacetone is 100:4. The hydrothermal treatment kettle is then quickly heated to 120° C. and reacted for 4.5 hours. The reaction was continuously stirred. After the reaction was completed, the ceramsite was aged for 6 hours to take out, washed with deionized water 5 times, and dried in a constant temperature drying oven at 120° C. for 3 hours to obtain a ceramsite filter material.
[0056] Example 4
[0057] The difference between this embodiment and embodiment 1 is that acetylacetone is not added during the hydrothermal treatment, and other conditions are the same as those in embodiment 1.
[0058] Comparative Example 1
[0059] The difference between this comparative example and Example 1 is that the microwave sintering furnace is replaced by a muffle furnace, and other conditions are the same as those in Example 1.
[0060] Comparative Example 2
[0061] The difference between this comparative example and Example 1 is that, in step 1), hydroxyapatite is not added during the sintering process of ceramsite, and other conditions are the same as those in Example 1.
[0062] Comparative Example 3
[0063] The difference between this comparative example and Example 1 is that 70 parts by weight of coal gasification slag, 5 parts by weight of coal gangue, 20 parts by weight of carbide slag and 15 parts by weight of hydroxyapatite are used to obtain sintered ceramsite, and other conditions are the same as those in Example 1.
[0064] Comparative Example 4
[0065] The difference between this comparative example and Example 1 is that the temperature of the pre-sintering treatment is 800° C., the temperature of the sintering treatment is 1000° C., and the other conditions are the same as those in Example 1.
[0066] Comparative Example 5
[0067] The difference between this comparative example and Example 1 is that the temperature of the pre-sintering treatment is 600° C., the temperature of the sintering treatment is 1100° C., and the other conditions are the same as those of Example 1.
[0068] Comparative Example 6
[0069] The difference between this comparative example and Example 1 is that the hydrothermal treatment described in step 2) is not performed on the sintered ceramsite, and other conditions are the same as those in Example 1.
[0070] Test Example 1
[0071] The ceramsite filter materials prepared in Examples 1-4 and Comparative Examples 1-6 were respectively tested for the defluorination effect of fluorine-containing wastewater. The specific testing method is as follows: 10 parts by weight of the ceramsite filter material is placed in a conical flask containing 250 parts by weight of fluorine-containing wastewater (the fluorine-containing wastewater is simulated wastewater obtained by adding sodium fluoride to deionized water, and the fluoride ion concentration is 7.38 mg / L), and adsorption is performed for 1 hour at room temperature. The test data are shown in Table 1;
[0072] Table 1
[0073]
[0074]
[0075] Test Example 2
[0076] The ceramsite filter material prepared in Example 2 was used in an actual fluorine-containing wastewater treatment process (the fluorine-containing wastewater was mine water from a coal mine in Ordos, Inner Mongolia, and its water quality composition is shown in Table 2). 10 parts by weight of the obtained ceramsite filter material was put into a conical flask containing 250 parts by weight of fluorine-containing wastewater. Under normal temperature conditions, a certain stirring rate was maintained. After adsorption for 1 hour, the water quality composition was shown in Table 2, and the defluorination rate was 80.57%.
[0077] Table 2 Water quality composition of mine water before and after adsorption
[0078]
[0079] Test Example 3
[0080] The ceramsite filter material prepared in Example 3 was used in an actual fluorine-containing wastewater treatment process (the fluorine-containing wastewater was mine water from a coal mine in Ordos, Inner Mongolia, and its water quality composition is shown in Table 3). 10 parts by weight of the obtained ceramsite filter material was put into a conical flask containing 250 parts by weight of fluorine-containing wastewater. Under normal temperature conditions, a certain stirring rate was maintained. After adsorption for 1 hour, the water quality composition is shown in Table 3, and the defluorination rate is 87.89%.
[0081] Table 3 Water quality composition of mine water before and after adsorption
[0082]
[0083] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a ceramsite filter material for treating fluorine-containing wastewater, characterized in that: include: 50-65 parts by weight of coal gasification slag, 10-15 parts by weight of coal gangue, 25-35 parts by weight of carbide slag and 5-10 parts by weight of hydroxyapatite are weighed and mixed to obtain a mixture, and then granulated and microwave sintered to obtain sintered ceramsite; wherein the heat treatment system of the microwave sintering is: firstly heating to 650-750° C. for pre-sintering treatment, and then heating to 1020-1080° C. for sintering treatment; The sintered ceramsite is immersed in a phosphate solution for hydrothermal treatment, and then subjected to aging treatment to obtain the ceramsite filter material.
2. The preparation method according to claim 1, characterized in that: The coal gasification slag contains 42-50wt% SiO2, 3-20wt% Al2O3, 2-18wt% CaO, 1-15wt% Fe2O3 and 10-30wt% carbon; And / or, the coal gangue contains SiO2: 40-60wt%, Al2O3: 35-50wt%; And / or, the carbide slag contains 35-60wt% CaO and 20-30wt% MgO.
3. The preparation method according to claim 1 or 2, characterized in that: The particle size of the coal gasification slag, coal gangue, carbide slag and hydroxyapatite is ≤100 μm; and / or, the binder used in the granulation step is a polyvinyl alcohol aqueous solution; and / or, the concentration of the binder used in the granulation step is 0.7-1wt%; and / or, the mass ratio of the mixture to the binder in the granulation step is 1:(17-25); And / or, the granulation step is followed by a drying process.
4. The preparation method according to any one of claims 1 to 3, characterized in that The heating rate of the pre-sintering treatment is 140-160°C / min; And / or, the duration of the pre-sintering treatment is 5-8 minutes; And / or, the heating rate of the sintering treatment is 45-55°C / min; And / or, the sintering treatment time is 5-10 min; And / or, the sintering process is followed by furnace cooling.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The duration of the aging treatment is ≥ 6h; And / or, the aging treatment is followed by washing and drying treatment; And / or, the strength of the sintered ceramsite is 5-10 MPa; And / or, the apparent porosity of the sintered ceramsite is 42-55%.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The hydrothermal treatment process comprises: firstly immersing the sintered ceramsite in deionized water until the pH value of the system is 9.5-10.5, and then adding phosphate and acetylacetone for hydrothermal treatment.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the sintered ceramsite to deionized water is 1:(6-8); And / or, the mass ratio of the sintered ceramsite to the phosphate is (40-60):1; And / or, the mass ratio of the deionized water to acetylacetone is 100:(2-4).
8. The preparation method according to any one of claims 1 to 7, characterized in that: The phosphate is diammonium phosphate and / or ammonium hydrogen phosphate; And / or, the immersion temperature is 60-80°C; And / or, the temperature of the hydrothermal treatment is 90-120°C; And / or, the duration of the hydrothermal treatment is 4-5 hours.
9. A ceramsite filter material for treating fluorine-containing wastewater, characterized in that: The ceramsite filter material is prepared by the method for preparing the ceramsite filter material for treating fluorine-containing wastewater according to any one of claims 1 to 8.
10. Use of the ceramsite filter material for treating fluorine-containing wastewater according to claim 9 in treating fluorine-containing wastewater.
Citation Information
Cited By
Method and system for preparing combustible gas and light ceramsite by smoldering coal gasification slag and product
CN121470989A